Download presentation

Presentation is loading. Please wait.

Published byMoses Murrin Modified about 1 year ago

1
Pisit Nakjai How to Calculate DelayTime

2
Loop1 delay1 = 4 Delayloop decfsz delay1,f1 MCdelay1 = 3 GotoDelayLoop2 MC decfsz delay1,f1 MC delay1 = 2 GotoDelayLoop2 MC decfsz delay1,f1 MC delay1 = 1 GotoDelayLoop2 MC decfsz delay1,f2 MC delay1 = 0 T = 3(4- 1)+2 T = 11

3
Full Loop1 delay1 = 0 Delayloop decfsz delay1,f1 MCdelay1 = 255 GotoDelayLoop2 MC … decfsz delay1,f1 MCdelay1 = 1 GotoDelayLoop2 MC decfsz delay1,f2 MC delay1 = 0 T = 3(256-1)+2 T = 767 MC

4
Second Loop delay2 = 3 Delayloop Full Loop1767 MC decfsz delay2,f1 MC delay2 = 2 GotoDelayLoop2 MC Full Loop1767 MC decfsz delay2,f1 MC delay2 = 1 GotoDelayLoop2 MC Full Loop1767 MC decfsz delay2,f2 MC delay2 = 0 T = (FullLoop1+3)(delay2-1)+2 T = (767+3)*3 +2 = 2303 MC

5
Second Full delay2 = 0 Delayloop Full Loop1767 MC decfsz delay2,f1 MC delay2 = 255 GotoDelayLoop2 MC Full Loop1767 MC decfsz delay2,f1 MC delay2 = 1 GotoDelayLoop2 MC Full Loop1767 MC decfsz delay2,f2 MC delay2 = 0 T = (FullLoop1+3)(256-1)+2 T = (767+3)*255 +2 = 195587 MC T n = 2+ (T n-1 + 3)(delay value -1)

6
MC with Full Mode

7
Example cnt1 = 171 cnt2 = 24 cnt3 = 6 DelayLoop decfsz cnt1,f GotoDelayLoop decfsz cnt2,f GotoDelayLoop decfsz cnt3,f GotoDelayLoop

8
Example T0 = 2+ (171-1)(3) = 512 T1 = 2+ (24-1)(767+3) = 17712 T2 = 2 + (6-1)(196352 + 3) = 981775 Total = T0+T1+T2 = 512+17712+981775 = 999999

Similar presentations

© 2017 SlidePlayer.com Inc.

All rights reserved.

Ads by Google